2014
DOI: 10.1017/s1041610214000015
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between small-scale nursing home care for people with dementia and staff's perceived job characteristics

Abstract: Background: Over the past few decades, new care models that are more resident-oriented and directed toward small-scale and homelike environments have been developed worldwide. The impact of these care models on the quality of life of residents has been studied. However, little research has been conducted to gain insight into how these new care models influence healthcare staff's work environment. This study focuses on the consequences of small-scale care on staff's perceived job characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
3
20
1
Order By: Relevance
“…We also assessed job resources to adjust for and examine their influence. Four job resources were included: (a) Presence/absence of educational opportunities (Ono, Nanbu, & Natsuhara, ); (b) appropriate feedback or support from nursing managers (Udou et al., ); (c) cooperation between nurses and care workers; and (d) recognition of organisational philosophy (Willemse, Depla, Smit, & Pot, ). First, we asked participants whether they had educational opportunities (e.g., ‘How many times did you have seminar programmes inside/outside of the hospital within the last 3 months?’).…”
Section: Methodsmentioning
confidence: 99%
“…We also assessed job resources to adjust for and examine their influence. Four job resources were included: (a) Presence/absence of educational opportunities (Ono, Nanbu, & Natsuhara, ); (b) appropriate feedback or support from nursing managers (Udou et al., ); (c) cooperation between nurses and care workers; and (d) recognition of organisational philosophy (Willemse, Depla, Smit, & Pot, ). First, we asked participants whether they had educational opportunities (e.g., ‘How many times did you have seminar programmes inside/outside of the hospital within the last 3 months?’).…”
Section: Methodsmentioning
confidence: 99%
“…Dutch certified nurse assistants are comparable to licensed practical/vocational nurses in the United States [37]. There are also nurse assistants (educational level 2), nurse aides (educational level 1) as well as some uneducated staff [38]. In many LTCFs, the lowest percentage of staff are RNs (educational level 4) and BRNs (educational level 5).…”
Section: Methodsmentioning
confidence: 99%
“…Te Boekhorst, Willemse, Depla, Eefsting, and Pot () found that job demands were lower and job control and social support were higher in small‐scale, homelike nursing homes in comparison with traditional nursing homes. Evidence shows that it is not only the type of small‐scale living environment that seems to impact the staff's well‐being, but also the dose or level of small scaledness that seems to matter (Verbeek, ; Willemse, Depla, Smit, & Pot, ). Willemse and colleagues () showed that if the long‐term care facility more strictly adhered to the key principles of small‐scale care, the staff perceived more decision‐making authority and less work pressure.…”
mentioning
confidence: 99%